Kedudukan dan Peranan Panglima Laot dalam Masyarakat Nelayan di Lhok Krueng Raya Aceh Besar (1978-2011) - Mujiburrahman Mujiburrahman (Jurnal Serambi Ekonomi dan Bisnis, 2017)
The purpose of this research is: (1) to know and examine the position and authority of Panglima Laot in fishing communities in Lhok Krueng Raya. (2) to know and examine the change of position and authority of Panglima Laot in fishing communities in Lhok Krueng Raya in 1978-2011. This study the authors used descriptive qualitative method that is descriptive answers observation and interviews from informants. The results of this study are: (1) the position of Panglima Laot in fishing communities in Lhok Krueng Raya as the top leader of indigenous laot community, is a prominent person among the fishermen. The authority of Panglima Laot to adjudicate disputes or disputes between fishermen is based on the prevailing customs. (2) the change of the position and role of Panglima Laot in Lhok Krueng Raya Aceh Besar as follows: in the past Panglima Laot played a role as a leader in the life of fishermen society, in the present time also still play a role in upholding custom law laot. The decreasing role of Panglima Laot is influenced by technological advances, change of views toward values by advanced education level and increasingly advanced awareness and understanding of religion.